2021
DOI: 10.3390/chemosensors9100291
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Methods for Hazardous Phenolic Compounds Based on Graphene and Conducting Polymers-Based Materials

Abstract: It has been known for years that the phenolic compounds are able to exert harmful effects toward living organisms including humans due to their high toxicity. Living organisms were exposed to these phenolic compounds as they were released into the environment as waste products from several fast-growing industries. In this regard, tremendous efforts have been made by researchers to develop sensing methods for the detection of these phenolic compounds. Graphene and conducting polymers-based materials have arisen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 252 publications
0
10
0
Order By: Relevance
“…With new generation biosensors, a more sensitive response is obtained by reducing the electroactive products to quinone, and the enzymatic reaction can be evidenced by a cathode current. Quinones can be reduced directly [ 71 , 72 ] or by redox mediators with catalytic activity [ 73 , 74 ], usually at a negative potential [ 45 ]. The intensity of the cathodic current is proportional to the concentration of phenolic compounds present in the sample.…”
Section: Tyrosinase-based Electrochemical Biosensors—characteristicsmentioning
confidence: 99%
“…With new generation biosensors, a more sensitive response is obtained by reducing the electroactive products to quinone, and the enzymatic reaction can be evidenced by a cathode current. Quinones can be reduced directly [ 71 , 72 ] or by redox mediators with catalytic activity [ 73 , 74 ], usually at a negative potential [ 45 ]. The intensity of the cathodic current is proportional to the concentration of phenolic compounds present in the sample.…”
Section: Tyrosinase-based Electrochemical Biosensors—characteristicsmentioning
confidence: 99%
“…However, PANI do have various shortcomings such as relatively low processing ability and mechanical strength. These inadequacies can be overcome, and their gas-sensing properties can be tailored substantially by forming graphene/conducting polymer hybrids [ 161 , 162 ]. Karouei et al recently studied the gas-sensing characteristics of a graphene/polyaniline nanocomposite under varying humidity conditions at room temperature.…”
Section: Applications Of Graphenementioning
confidence: 99%
“…Linear conducting polymers including polypyrrole (PPy), polyaniline (PANI), polyfuran (PF), and polythiophene (PTh) have been equally examined theoretically and experimentally to inspect their sensing properties 20,21 . Literature study showed that conducting polymers have been used for the detection of hydrazine, methanol, ethanol, halogens, hydrogen halides, H 2 O, CO 2 , CH 4 , NH 3 , and other compounds [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%